A multi-stage mixed crystal aluminum matrix composite material, a mixed crystal ratio controllable preparation method and application thereof

CN118326209BActive Publication Date: 2026-10-09HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410392599.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-02
Publication Date
2026-10-09
Estimated Expiration
2044-04-02

AI Technical Summary

Technical Problem

然而随着增强相含量的增加,团聚趋势增大,复合材料的强度得到提升的同时塑性大幅降低,直至整体脆性断裂,强度-塑(韧)性倒置关系成为亟待解决的金属基复合材料的发展瓶颈

Benefits of technology

[0025] (1) This invention fully utilizes the advantages of different reinforcing phases by using a partitioned ball milling method. High-energy ball milling is used to obtain a nanocrystalline aggregate with internally distributed crystals by aluminum powder and hard nanoparticles. Medium-energy ball milling is used to obtain a micro-nanocrystalline aggregate uniformly coated with flexible nanocarbon while ensuring the integrity of the nanocarbon structure. Finally, pure metal powder is mixed with the composite powder of the above two regions to introduce a coarse-grained region that is beneficial to the plasticity of the material. Finally, a multi-level mixed crystal aluminum-based composite material is obtained with hard nanoparticles enriched in the nanocrystalline region for reinforcement, flexible nanocarbon grain boundary distribution in the micro-nanocrystalline region for transition buffer, and Al coarse-grained region for plasticity assistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118326209B_ABST
    Figure CN118326209B_ABST
Patent Text Reader

Abstract

A kind of multistage mixed crystal aluminum matrix composite material and its mixed crystal ratio controllable preparation method and application.The present application belongs to the field of metal matrix composite material preparation.The present application fully develops the advantage of different property reinforcing phase by the way of partition ball milling,adopts high-energy ball milling to aluminum powder and hard nano-particle,so as to obtain intracrystalline distribution of nano-crystalline collection;Adopting medium-energy ball milling to aluminum powder and flexible nanocarbon,obtaining flexible nanocarbon uniformly coated micro-nano-crystalline collection on the premise of ensuring the integrity of nanocarbon structure,finally by mixing pure metal powder with the above two zone composite powder, introducing coarse-grained zone conducive to material plasticity, ultimately obtaining hard nano-particle enriched nano-crystalline zone reinforcement, flexible nanocarbon grain boundary distribution micro-nano-crystalline zone transition buffer, Al coarse-grained zone plasticity auxiliary multistage mixed crystal aluminum matrix composite material. The method of the present application has high controllability and low preparation cost. It can be used for preparing multistage mixed crystal metal matrix composite materials based on other metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal matrix composite material preparation, specifically relating to a multi-level mixed crystal aluminum matrix composite material and its preparation method and application with controllable mixed crystal ratio. Background Technology

[0002] Traditional aluminum matrix composites emphasize achieving a homogeneous composite structure, pursuing a uniform distribution of the reinforcing phase in the matrix to avoid agglomeration. However, with the increase of the reinforcing phase content, the agglomeration tendency increases, resulting in a significant decrease in plasticity while improving the strength of the composite material, eventually leading to brittle fracture. The inverted strength-plasticity (toughness) relationship has become a bottleneck in the development of metal matrix composites that urgently needs to be addressed. Based on the concept of non-homogeneous configuration, new composite material design ideas such as coarse-grained and fine-grained configurations have been proposed. However, practical research has revealed many problems in the matching of multiple types of reinforcement and stress compatibility in these new composite materials, which greatly affect the potential for breakthroughs in material properties.

[0003] Currently, there are the following shortcomings in coarse and fine crystal structure composite materials: (1) It is difficult to control the ratio of coarse and fine crystals in coarse and fine crystal structure composite materials, and the controllability of the preparation process is low; (2) The strength difference between the fine and coarse crystal regions in bimodal structure composite materials is too large, and there is obvious strain incompatibility, which leads to premature cracking at the interface between hard and soft regions; (3) Currently, bimodal structure materials use a single reinforcing phase, and the fine crystal structure comes from the high-energy ball milling of the reinforcing phase and aluminum powder, while the coarse crystal region is pure metal. The partition design and preparation process are simple and cannot meet the fine requirements for performance improvement. Summary of the Invention

[0004] To overcome the above-mentioned technical problems, the present invention provides a multi-level mixed crystal aluminum-based composite material, a method for preparing the mixed crystal ratio controllable, and its application.

[0005] The technical solution of the present invention is as follows:

[0006] One objective of this invention is to provide a multi-level mixed-crystal aluminum-based composite material, wherein the aluminum-based composite material includes regionally distributed nanocrystalline regions, micro-nanocrystalline regions, and micron-crystalline regions. The nanocrystalline regions are regions enriched with hard nanoparticles, which are located inside pure aluminum grains. The micro-nanocrystalline regions are regions enriched with flexible nano-carbon materials, which are located at grain boundaries. The micron-crystalline regions are pure aluminum crystal regions.

[0007] Further specified, the average grain size of the nanocrystalline region is less than 400 nm, the grain size of the micro / nanocrystalline region is 0.5–2 μm, and the grain size of the micron-crystalline region is 5–20 μm.

[0008] Further specifying, the hard nanoparticles are one of silicon carbide (SiC), silicon nitride (Si3N4), and aluminum oxide (Al2O3), and the size of the hard nanoparticles is 10-50 nm.

[0009] Further specifying, the flexible carbon nanomaterial is selected from one of graphene nanosheets, carbon nanotubes, carbon nanofibers, and carbon nanospheres, and the flexible carbon nanomaterial has at least one dimension with a size less than 100 nm.

[0010] Further specified, the content of hard nanoparticles is 1–10 vol.%, and the content of flexible carbon nanomaterials is 0.5–3 vol.%.

[0011] Further specified, the multi-level mixed crystal aluminum matrix composite material has a tensile strength ≥285.4MPa, a yield strength ≥240.3MPa, and an elongation ≥18.5%.

[0012] The second objective of this invention is to provide a method for preparing a multi-level mixed-crystal aluminum-based composite material with a controllable mixed-crystal ratio, which is carried out according to the following steps:

[0013] S1: Hard nanoparticles and aluminum powder are mixed at low speed until uniform, and then subjected to high-energy ball milling to uniformly disperse the hard nanoparticles inside the aluminum grains to obtain nanocomposite powder.

[0014] S2: After mixing the flexible carbon nanomaterial with aluminum powder at low speed until uniform, the mixture is ball-milled at medium energy to obtain micro-nano composite powder coated with flexible carbon nanomaterial.

[0015] S3: Nanocomposite powder, micro-nanocomposite powder and aluminum powder are first ball-milled at low speed, and then subjected to spark plasma sintering and hot extrusion to obtain multi-level mixed crystal aluminum-based composite material.

[0016] Further specified, the speed of low-speed mixing in S1 is 100-250 rpm, and the time is 1-8 hours.

[0017] Further specified, the high-energy ball mill in S1 has a rotation speed of 300-800 rpm and a time of 5-15 h.

[0018] Further specified, the speed of low-speed mixing in S2 is 40-200 rpm, and the time is 3-20 h.

[0019] Further specifying, the rotation speed of the medium-energy ball mill in S2 is 250-300 rpm, and the time is 1-5 h.

[0020] Further specified, the rotation speed of the S3 low-speed ball mill is 150-450 rpm, and the time is 1-20 h.

[0021] Further specified, the volume ratio of nanocomposite powder, micro-nanocomposite powder and aluminum powder in S3 is 1:(0.8-1):(0.2-0.5).

[0022] The third objective of this invention is to provide an application of the above method in the preparation of multi-level mixed crystal metal matrix composites, wherein the metal matrix is ​​one or more of Al, Mg, Fe, Ti, and Cu.

[0023] The fourth objective of this invention is to provide an application of multi-level mixed crystal aluminum matrix composite material in the fields of aerospace, energy, marine engineering and transportation.

[0024] The advantages of this invention compared to existing technologies are:

[0025] (1) This invention fully utilizes the advantages of different reinforcing phases by using a partitioned ball milling method. High-energy ball milling is used to obtain a nanocrystalline aggregate with internally distributed crystals by aluminum powder and hard nanoparticles. Medium-energy ball milling is used to obtain a micro-nanocrystalline aggregate uniformly coated with flexible nanocarbon while ensuring the integrity of the nanocarbon structure. Finally, pure metal powder is mixed with the composite powder of the above two regions to introduce a coarse-grained region that is beneficial to the plasticity of the material. Finally, a multi-level mixed crystal aluminum-based composite material is obtained with hard nanoparticles enriched in the nanocrystalline region for reinforcement, flexible nanocarbon grain boundary distribution in the micro-nanocrystalline region for transition buffer, and Al coarse-grained region for plasticity assistance.

[0026] (2) The purpose of this invention is to achieve precise control of design requirements by selectively choosing different types, contents, distributions, and process parameters of reinforcing phases based on the microstructure and performance requirements of different zones, leveraging the high designability of aluminum-based composite materials. Through more precise hierarchical structural design and the optimization potential of different reinforcing phases, the composite material achieves a multi-factor comprehensive strengthening effect, thereby achieving the goal of simultaneously improving strength and plasticity, and providing a new technical approach for obtaining high-strength and tough composite materials.

[0027] (3) Based on the specific partition structure design of the ball milling stage, the present invention strengthens the characteristics of each partition through large plastic deformation. The strong extrusion during the deformation process promotes the internal distribution of hard nanoparticles. As the shearing effect increases, the graphene nanosheets peel off along the extrusion direction to obtain further dispersion and streamline distribution. Finally, a high-strain compatibility aluminum-based composite material with different partitions of oriented distribution is obtained.

[0028] (4) Based on the organizational and performance requirements of different partitions, this invention selects different types, contents, and distributions of reinforcing phases, as well as different process parameters, to achieve precise control of design requirements. It can perform independent partition design and preparation for grains of different size levels, with high process controllability, accurate control of the content and size of grains at each level, wide applicability, large tolerance, low preparation cost, and is conducive to promotion and application. Attached Figure Description

[0029] Figure 1This is a schematic diagram of the ball milling process for the multi-stage mixed-crystal aluminum-based composite material of the present invention;

[0030] Figure 2 This is a metallographic photograph of the extruded Com40-40-20 sample from Example 1;

[0031] Figure 3 This is an EBSD grain morphology image of the extruded Com40-40-20 sample from Example 1;

[0032] Figure 4 This is a transmission electron microscope (TEM) HADDF image of the extruded Com40-40-20 sample from Example 1;

[0033] Figure 5 The transmission electron microscope shows the Si element distribution of the extruded Com40-40-20 sample from Example 1.

[0034] Figure 6 This is a bright-field transmission electron microscope image of the extruded Com40-40-20 sample from Example 1;

[0035] Figure 7 These are the tensile mechanical property curves of the extruded samples of Example 1 and Comparative Example 1. Detailed Implementation

[0036] The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used in the following detailed description, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such a composition, step, method, article, or apparatus.

[0037] This invention provides a method for preparing a multi-level mixed-crystal aluminum-based composite material with controllable mixed crystal ratio, specifically comprising the following steps:

[0038] (1) Hard nanoparticles and aluminum powder are mixed at low speed until uniform and then subjected to high-energy ball milling to make the hard nanoparticles uniformly dispersed inside the aluminum grains to obtain nanocomposite powder.

[0039] (2) After mixing the flexible nano-carbon material with aluminum powder at low speed until uniform, the mixture is ball-milled at medium energy to obtain micro-nano composite powder coated with flexible nano-carbon material.

[0040] (3) The nanocomposite powder, micro-nanocomposite powder and aluminum powder are ball-milled at low speed to obtain multi-level mixed crystal composite powder.

[0041] (4) The multi-level mixed crystal composite powder is subjected to discharge plasma sintering and hot extrusion to obtain a multi-level mixed crystal aluminum matrix composite material.

[0042] In the above specific embodiments, the hard nanoparticles mentioned in step (1) are one of silicon carbide (SiC), silicon nitride (Si3N4), and aluminum oxide (Al2O3), with a size of 10-50 nm. The low-speed mixing speed is 100-250 rpm, and the time is 1-8 h. The high-energy ball milling speed is 300-800 rpm, and the time is 5-15 h.

[0043] In the above specific embodiments, the flexible carbon nanomaterial mentioned in step (2) is selected from one of graphene nanosheets, carbon nanotubes, carbon nanofibers, and carbon nanospheres, and has at least one dimension smaller than 100 nm. The low-speed mixing speed is 40-200 rpm, and the time is 3-20 h. The medium-energy ball milling speed is 250-300 rpm, and the time is 1-5 h.

[0044] In the above specific embodiments, the content of hard nanoparticles in the multi-level mixed crystal composite powder in step (3) is 1-10 vol.%, and the content of flexible nano-carbon material is 0.5-3 vol.%. The volume ratio of nano-composite powder, micro-nano composite powder and aluminum powder is 1:(1-0.8):(0.2-0.5). The rotation speed of the low-speed ball mill is 150-450 rpm, and the time is 1-20 h.

[0045] In the above specific embodiments, the grinding balls used in the ball mill in steps (1), (2) and (3) are all stainless steel balls, and the ball-to-material ratio is (5-20):1.

[0046] In the above specific embodiment, the sintering temperature in step (4) is 400-550℃, the pressure is 40-100MPa, and the time is 5-15min. The hot extrusion temperature is 300-500℃, and the hot extrusion ratio is (6-36):1.

[0047] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0048] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.

[0049] In the following embodiments, the grinding balls used in the ball mills are all stainless steel balls, and the ball-to-material ratio is 15:1.

[0050] Example 1: The method for controlling the mixed crystal ratio of the multi-stage aluminum-based composite material in this example is carried out according to the following steps:

[0051] (1) Mix the nano-silicon carbide particles SiCnp (particle size 20-80nm) with aluminum powder (particle size 5-25μm) at 200rpm for 5h until uniform, and then ball mill at 300rpm for 10h to make the nano-silicon carbide particles uniformly dispersed in the interior of aluminum grains to obtain Al-SiCnp nanocomposite powder.

[0052] (2) Graphene nanosheets GNS (thickness of 5-10 nm, average diameter of 1.6 μm) and aluminum powder (particle size of 5-25 μm) were mixed at 200 rpm for 5 h until uniform, and then ball-milled at 300 rpm for 2 h to obtain Al-GNS micro-nano composite powder coated with graphene nanosheets.

[0053] (3) The nanocomposite powder, micro-nanocomposite powder and aluminum powder were ball-milled at 200 rpm for 5 h in a volume ratio of 40:40:20 to obtain multi-level mixed crystal composite powder, wherein the volume fraction of aluminum powder was 97 vol%, the volume fraction of graphene nanosheets GNS was 1.5 vol%, and the volume fraction of nano silicon carbide particles SiCnp was 1.5 vol%.

[0054] (4) The multi-level mixed crystal composite powder is placed in a mold for vacuum discharge plasma sintering (SPS) at a temperature of 530°C and a pressure of 50 MPa. The temperature and pressure are maintained for 5 minutes. Then it is loaded into an extrusion mold for preheating and hot extrusion at 490°C with an extrusion ratio of 15:1. Finally, the multi-level mixed crystal aluminum matrix composite material, abbreviated as Com40-40-20, is obtained.

[0055] Figure 1 This is a schematic diagram of the ball milling process for multi-level mixed-crystal aluminum matrix composites. The three-peak hybrid configuration (SiCnp+GNS) / Al composite material is designed with a three-level grain structure: Level 1 (nanocrystalline), Level 2 (micro-nanocrystalline), and Level 3 (microcrystalline). A segmented ball milling process is adopted, with targeted ball milling schemes designed for each grain partition structure. Al-SiCnp and Al-GNS mixed powders are ball milled with high energy and medium energy respectively to obtain Level 1 and Level 2 grains. Then, the Level 1 (Al-SiCnp) and Level 2 (Al-GNS) grain composite powders are mixed uniformly with unball-milled microcrystalline pure Al powder at a volume ratio of 40:40:20 to obtain the final grain-graded (SiCnp+GNS) / Al composite powder. Subsequently, composite rods are obtained by spark plasma sintering (SPS) and subsequent hot extrusion deformation.

[0056] Figure 2These are metallographic images of the extruded Com40-40-20 sample from Example 1. Hot extrusion deformation was used as a secondary deformation process to densify the composite material, further disperse the reinforcing phase within the matrix, and adjust the configuration of each zone, thereby improving the bonding strength. After hot extrusion deformation, defects in the aluminum matrix and agglomeration of the reinforcing phase were significantly reduced. The Al-SiCnp region was significantly elongated along the extrusion direction, and the dispersion of the SiCnp reinforcing phase was significantly improved. Al-GNS and Al regions were interspersed within the Al-SiCnp regions. The Al-SiCnp regions in the Com40-40-20 composite material were slender and uniformly distributed.

[0057] Figure 3 The image shows the EBSD grain morphology of the extruded Com40-40-20 sample from Example 1. It can be seen that the grain distribution of the three-peaked composite material in Example 1 exhibits obvious mixed-crystal characteristics. Al-GNS micro / nanocrystalline regions and micron regions are encapsulated around the Al-SiCnp nanocrystalline region, showing significant lamellar structure and a transition from coarse to fine grains. The average size of the Al grains in the three regions was statistically analyzed and mainly divided into three levels: ① Nanocrystalline region (average grain size ~386nm), with grain sizes below 400nm; ② Micro / nanocrystalline region (average grain size ~667nm), with grain sizes ranging from 500nm to 1μm; ③ Microcrystalline region (average grain size ~5.27μm), with grain sizes ranging from 5 to 12μm. The three regions with different grain sizes are interspersed.

[0058] Figure 4 and Figure 5 The transmission electron microscope (TEM) HADDF image and Si elemental distribution of the extruded Com40-40-20 sample from Example 1 reveal that the composite material exhibits a clear distribution of nanocrystalline, micro-nanocrystalline, and microcrystalline regions. Figure 4 The SiCnp distribution exhibits strong regionality. Figure 5 The Al-SiCnp nanocrystalline region is mainly concentrated in the nanocrystalline region. This is because, during the ball milling stage, under the influence of high ball milling energy, most of it is surrounded within the cold-welded aluminum particles and dispersed within them. Furthermore, due to the significant strength difference between the Al-SiCnp cold-welded fine-grained aluminum particles and the powder in the other two regions, SiCnp is difficult to disperse into other regions during the final ball milling stage and subsequent hot extrusion, thus forming distinct zoning. The Al-SiCnp nanocrystalline region, adjacent to the Al-GNS micro / nanocrystalline region and the micron-crystalline region of pure Al grains, constitutes a distinct three-peak mixed crystal distribution.

[0059] Figure 6The image shows the reinforcing phase distribution under transmission electron microscopy (TEM) of the extruded Com40-40-20 sample from Example 1. In the nanocrystalline region (Al-SiCnp), SiCnp is dispersed within the Al grains, which are primarily nano-equiaxed crystals. These results demonstrate that a multi-level mixed-crystal (SiCnp+GNS) / Al composite material was successfully prepared using the established powder metallurgy process.

[0060] Comparative Example 1:

[0061] The difference between this comparative example and Example 1 is that no partitioning design is performed. All other steps and parameters are the same as in Example 1.

[0062] The specific steps are as follows: Nano-sized silicon carbide particles, graphene nanosheets, and aluminum powder are ball-milled together, first at 200 rpm for 5 hours, then at a high speed of 300 rpm for 2 hours, to obtain a homogeneous hybrid reinforced aluminum matrix composite material, abbreviated as Al-1.5SiCnp-1.5GNS.

[0063] The mechanical properties of the composite materials prepared in Example 1 and Comparative Example 1 were tested (GB / T 228.1-2010), and the results are as follows. Figure 1 As shown in Table 1, it can be seen that the multi-level mixed crystal composite material Com40-40-20 has significantly improved strength and plasticity compared to aluminum matrix composites with a more uniform structure.

[0064] Table 1

[0065]

[0066] In summary, this invention achieves precise control over grain size at different levels by selectively controlling ball milling of each crystal region. First, high-energy ball milling yields nanocrystalline regions with intragranular distribution, and medium-energy ball milling yields micro-nano transitional crystal regions with flexible GNS grain boundaries. Finally, a designed quantitative composite powder of each crystal region is ball-milled and mixed with coarse-grained aluminum powder to obtain a multi-level mixed-crystal composite powder with a defined proportion of the three types of crystal regions. Finally, sintering and large plastic deformation processes result in a multi-level mixed-crystal aluminum-based composite material with interbedded multi-level crystal regions arranged in a streamlined manner. Compared to homogeneous composite materials, the multi-level mixed-crystal aluminum-based composite material exhibits a reasonable transition between coarse and fine grains, generating additional back stress reinforcement during coordinated deformation. It also possesses higher strain descriptivity than ordinary bimodal materials, achieving a simultaneous improvement in the strength and plasticity of the composite material.

[0067] The above description is merely a preferred embodiment of the present invention. These specific embodiments are different implementations based on the overall concept of the present invention, and the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A multi-level mixed-crystal aluminum-based composite material, characterized in that, It includes regionally distributed nanocrystalline, micro-nanocrystalline, and micron-crystalline regions. The nanocrystalline region is a region rich in hard nanoparticles, which are located inside pure aluminum grains. The micro-nanocrystalline region is a region rich in flexible carbon nanomaterials, which are located at grain boundaries. The micron-crystalline region is a pure aluminum crystal region. The average grain size of the nanocrystalline region is less than 400 nm, the grain size of the micro-nanocrystalline region is 0.5~2 μm, and the grain size of the micron-crystalline region is 5~20 μm. The hard nanoparticles are one of SiC, Si3N4, and Al2O3, and the size of the hard nanoparticles is 10-50 nm. The flexible carbon nanomaterials are selected from one of graphene nanosheets, carbon nanotubes, carbon nanofibers, and carbon nanospheres, and the flexible carbon nanomaterials have at least one dimension smaller than 100 nm. The content of hard nanoparticles is 1~10 vol.%, and the content of flexible carbon nanomaterials is 0.5~3 vol.%.

2. The composite material according to claim 1, characterized in that, The multi-level mixed crystal aluminum matrix composite has a tensile strength ≥285.4MPa, a yield strength ≥240.3MPa, and an elongation ≥18.5%.

3. A method for preparing a multi-stage mixed-crystal aluminum-based composite material with controllable mixed crystal ratio according to any one of claims 1-2, characterized in that, Follow these steps: S1: Hard nanoparticles and aluminum powder are mixed at low speed until uniform, and then subjected to high-energy ball milling to uniformly disperse the hard nanoparticles inside the aluminum grains to obtain nanocomposite powder. S2: After mixing the flexible carbon nanomaterial with aluminum powder at low speed until uniform, the mixture is ball-milled at medium energy to obtain micro-nano composite powder coated with flexible carbon nanomaterial. S3: Nanocomposite powder, micro-nanocomposite powder and aluminum powder are first ball-milled at low speed, and then subjected to spark plasma sintering and hot extrusion to obtain multi-level mixed crystal aluminum-based composite material.

4. The method according to claim 3, characterized in that, The speed of low-speed mixing in S1 is 100~250 rpm and the time is 1~8h, while the speed of high-energy ball milling is 300~800 rpm and the time is 5~15h.

5. The method according to claim 3, characterized in that, The speed of S2 low-speed mixing is 40~200 rpm and the time is 3~20h, while the speed of medium-energy ball milling is 250~300 rpm and the time is 1~5h.

6. The method according to claim 3, characterized in that, The rotation speed of the S3 medium-low speed ball mill is 150~450 rpm, the time is 1~20h, and the volume ratio of nanocomposite powder, micro-nanocomposite powder and aluminum powder is 1:(0.8-1):(0.2-0.5).

7. The application of the method according to any one of claims 3-6 in the preparation of multi-level mixed-crystal metal matrix composites, characterized in that, The metallic matrix is ​​one or more of Al, Mg, Fe, Ti, and Cu.

8. The application of the multi-level mixed crystal aluminum matrix composite material according to any one of claims 1-2 in the fields of aerospace, energy, marine engineering and transportation.

Citation Information

Patent Citations

  • Nano-reinforced metal-based composite material with three-peak characteristic

    CN111519073A

  • Double-scale hybrid particle reinforced aluminum-based composite material for automobile and preparation method of double-scale hybrid particle reinforced aluminum-based composite material

    CN113718142A